Revisi Dalam Penerjemahan - Pamungkas, Muhammad Ersan Pamungkas (Jurnal Penerjemahan, 2018)
Translation can become a long process, which can begin from pre-translation phase, translation phase itself, and post translation phase. Each phase may also consist of more than one part. One of the parts in the post-translation process is revising, which mainly aims to improve quality of the translation. Nevertheless, the question remains as to what can be revised in the revision of a translation. Therefore, this paper tries to investigate aspects in translation that can be revised by a reviser. This research adopts a qualitative method with a comparative conceptual method, while the source data consists of selected sentences from four English translations of online news articles on the official website of the Cabinet Secretariat of the Republic of Indonesia. Several sentences from the four papers are randomly selected to be further discussed in this paper. The result of this paper shows that there are at least four aspects that can be revised in the translation of those articles, namely accuracy, grammatical errors, as well as punctuation and typographical errors, and style. Keywords: translation, revision, reviser, online newspaper articles.